A case report of adenofibroma arising from the seminal vesicle: A rare giant pelvic mass - Lu, Youyi; Sun, Di; Wu, Jitao (Frontiers in Oncology, 2022)
Primary seminal vesicle tumors are extremely rare.Several rare pathological types of primary seminal vesicle tumors have been reported,such as adenocarcinoma, but there is no report on adenofibroma.We report the first case of adenofibroma arising from the seminal vesicle.A 50-year-old man,with no history or clinical evidence of any other tumors, accidentally found a pelvic mass during an ultrasound examination. As the mass grew,the patient developed mild constipation, without genitourinary or other symptoms.All laboratory examinations were normal.MRI of the pelvis revealed a mixed density,measuring 11.7×9.9×8.2cm,well circumscribed mass.The rectum, bladder,prostate and lymph nodes were normal.We successfully performed the open surgery and removed the mass.Histopathological results confirmed that the mass was a primary seminal vesicle adenofibroma.In literature,we found that for biphasic differentiated tumors,it is easy to reduce the accuracy of pathological diagnosis because of insufficient puncture.Therefore, preoperative puncture biopsy for seminal vesicle tumors should be investigated further.